Cultural Memory as a Means of Understanding Transculturality - Talakvadze, Tea; Lobjanidze, Ivlita ("Intercultural Dialogues" Transactions, 2021)
Memory studies have been particularly active since the second half of the 20th century and include a mix of fields of culturology, social psychology, media archeology, political philosophy, and comparative literature. Memory studies have formed the basis of both collective and individual identity studies, as well as the study of psycho-social factors in understanding traumatic memory and attempts to overcome trauma. Memory studies have activated an in-depth analysis of the construction of national and cultural identities and brought them into the context of transnational and transcultural studies.Based on the above, the purpose of this report is to provide a transcultural understanding of national culture based on the study of cultural memory, which is primarily based on the study of national identity and the analysis of the compositional nature of common / shared myths.